An investigation into class observation for professional development by teachers of english at some high school in Ca Mau : - Tô, Kim Thuý (Trường đại học Cần Thơ, 2010)
The study aimed (1) to investigate the high school English teachers' perceptions toward class observation for professional development and (2) to examine the real class observation practice in high school context to provide the implications for effective class observation practice.